2013
DOI: 10.1371/journal.pone.0059725
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of IRS1 at Serine 307 in Response to Insulin in Human Adipocytes Is Not Likely to be Catalyzed by p70 Ribosomal S6 Kinase

Abstract: The insulin receptor substrate-1 (IRS1) is phosphorylated on serine 307 (human sequence, corresponding to murine serine 302) in response to insulin as part of a feedback loop that controls IRS1 phosphorylation on tyrosine residues by the insulin receptor. This in turn directly affects downstream signaling and is in human adipocytes implicated in the pathogenesis of insulin resistance and type 2 diabetes. The phosphorylation is inhibited by rapamycin, a specific inhibitor of mammalian target of rapamycin (mTOR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
(37 reference statements)
3
22
0
Order By: Relevance
“…6B, blue). Strikingly, the alignment of the doseresponse curves in the signaling cassette IRS1-Grb2-Sos-RasRaf-Mek1/2-ERK1/2 is in sharp contrast to the 10-fold increase in insulin sensitivity 4 in the parallel IRS1-PI3K-PKB-AS160 cassette mediating insulin control of glucose uptake (3). The function of this difference in insulin signal transduction is not known, but it has been shown in yeast cells that alignment of doseresponse curves, due to negative feedback signals, in MAPK signaling allows for higher fidelity in signal transmission (48).…”
Section: Phosphorylation Of Erk1/2 In Response To Different Concentramentioning
confidence: 99%
See 1 more Smart Citation
“…6B, blue). Strikingly, the alignment of the doseresponse curves in the signaling cassette IRS1-Grb2-Sos-RasRaf-Mek1/2-ERK1/2 is in sharp contrast to the 10-fold increase in insulin sensitivity 4 in the parallel IRS1-PI3K-PKB-AS160 cassette mediating insulin control of glucose uptake (3). The function of this difference in insulin signal transduction is not known, but it has been shown in yeast cells that alignment of doseresponse curves, due to negative feedback signals, in MAPK signaling allows for higher fidelity in signal transmission (48).…”
Section: Phosphorylation Of Erk1/2 In Response To Different Concentramentioning
confidence: 99%
“…We have taken a systems approach to the investigation of the mechanisms of insulin resistance, and we have previously described the branch of the insulin signaling network that leads to control of glucose uptake in human adipocytes, normally and in T2D (1)(2)(3)(4) (Fig. 1).…”
mentioning
confidence: 99%
“…Also in isolated human adipocytes, insulinstimulated phosphorylation of IRS1 at Ser 307 is affected by rapamycin treatment [66,67]. The phosphorylation of IRS1 at Ser 307 has been suggested to occur downstream of S6K, but we have shown that it is unlikely that S6K is the kinase for phosphorylation of IRS1 at Ser 307, at least in human adipocytes [68]. We have observed a positive effect of phosphorylation of IRS1 at Ser 307 on the phosphorylation of IRS1 at Tyr in human adipocytes: rapamycin reduces also the phosphorylation of IRS1 at Tyr [66].…”
Section: Regulatory Feedbacks Control Insulin Signaling Via Irs1mentioning
confidence: 66%
“…One of the most important consequences of the initiated signaling cascade is the recruitment of Glucose Transporter 4 (GLUT4) containing vesicles into the plasma membrane, which results in an increased uptake of glucose into the adipocyte. In Paper II, we focus on a particular aspect of the green arrow in Figure 32, namely the positive feedback from a downstream component (here shown as mTOR) up to IRS1.This feedback had been shown in other cell types to come directly from S6K, but experimental evidence suggest that this was not the case in human adipocytes [127]. In Paper II, we investigate whether this conclusion held up under further scrutiny, and which conditions must apply for it to be considered valid.…”
Section: Insulin Signaling System In Human Adipocytesmentioning
confidence: 99%
“…We then applied this specific methodology to re-interpret data pertaining to the phosphorylation of IRS1 on serine residue 307. It had previously been shown that in primary human adipocytes, unlike other known cell lines, S6K inhibition by DN transfection did not result in any effect on IRS1-ser307 phosphorylation [127]. This lack of response was used as evidence to suggest that S6K was unlikely to be the kinase responsible for IRS1-ser307 phosphorylation in this cell type.…”
mentioning
confidence: 96%